Factors Influencing the Success of Educational Administration under the New Distance Learning via Satellite Project (New DLTV) in Small Schools under the Uttaradit Primary Educational Service Area Office 1 - Phangkum, Sumittra; Pansri, Omthajit (Journal of Graduate MCU KhonKaen Campus, 2025)
The objective of this research was to achieve four aims: (1) to examine the factors influencing educational administration, (2) to assess the level of factors contributing to the success of educational administration, (3) to analyze the relationships among the influencing factors, and (4) to identify the key predictive variables and develop a predictive equation for the success of educational administration under the New Distance Learning via Satellite Project (New DLTV) in small schools under the Uttaradit Primary Educational Service Area Office 1. Thus, in this research, the sample consisted of 95 small schools participating in the New Distance Learning via Satellite Project (New DLTV). A total of 298 participants, including school administrators and teachers, were selected through random sampling. The research instrument employed was a questionnaire. Data were analyzed using percentage, mean, standard deviation, and multiple regression analysis. The results of the analysis revealed that: 1) The overall factors Influencing the success of Educational Administration were rated a great extent across all aspects, including personnel development, leadership, administrative management, and information technology, respectively. 2) The overall level of success in of Educational Administration was also high, with a mean score of 4.30, encompassing teaching and learning management, student quality, and as well as administrative management. 3) The relationships between the factors influencing the success of the New Distance Learning via Satellite Project (New DLTV) Educational Administration showed Pearson’s correlation coefficients ranging from 0.636 to 0.696, which were statistically significant at the .01 level. 4) The predictive dominance of the factors influencing the success of Educational Administration under the New Distance Learning via Satellite Project (New DLTV) in Small Schools revealed that a coefficient of determination (R²) of 0.549, indicating a predictive dominance of 54.90%. The best-fit predictive equations were: Unstandardized score: 1.407 + 0.339X2 + 0.316X4 Standardized score: 0.405ZX2 + 0.387ZX4